Model-based assessment and neural correlates of spatial memory deficits in mild cognitive impairment - Weigard, Alexander S. (Neuropsychologia, 2019)
Mild cognitive impairment (MCI) is characterized by subjective and objective memory impairments within the context of generally intact everyday functioning. Such memory deficits are typically thought to arise from medial temporal lobe dysfunction; however, differences in memory task performance can arise from a variety of altered processes (e.g., strategy adjustments) rather than, or in addition to, “pure” memory deficits. To address this problem, we applied the linear ballistic accumulator (LBA: Brown & Heathcote, 2008) model to data from individuals with MCI (n=18) and healthy older adults (HOA; n=16) who performed an object-location association memory retrieval task during functional magnetic resonance imaging (fMRI). The primary goals were to 1) assess between-group differences in model parameters indexing processes of interest (memory sensitivity, accumulation speed, caution and time spent on peripheral perceptual and motor processes) and 2) determine whether differences in model-based metrics were consistent with fMRI data. The LBA provided evidence that, relative to the HOA group, those with MCI displayed lower sensitivity (i.e., difficulty discriminating targets from lures), suggestive of memory impairment, and displayed higher evidence accumulation speed and greater caution, suggestive of increased arousal and strategic changes in this group, although these changes had little impact on MCI-related accuracy differences. Consistent with these findings, fMRI revealed reduced activation in brain regions previously linked to evidence accumulation and to the implementation of caution reductions in the MCI group. Findings suggest that multiple cognitive mechanisms differ during memory performance in MCI, and that these mechanisms may explain neuroimaging alterations outside of the medial temporal lobes.